JUVENILE RHEUMATOID ARTHRITIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Juvenile rheumatoid arthritis is a chronic autoimmune disease in children. This disease appears mainly in adolescence, that is, in children under the age of sixteen. Juvenile rheumatoid arthritis damages joints, muscles, and other tissues as a result of a malfunctioning immune system. This disease can significantly reduce the quality of life of children, so early detection and proper treatment are very important.